2020
DOI: 10.1103/physrevresearch.2.042017
|View full text |Cite
|
Sign up to set email alerts
|

Swarming transitions in hierarchical societies

Abstract: Social hierarchy is central to decision-making in the coordinated movement of many swarming species. Here we propose a hierarchical swarm model in the spirit of the Vicsek model of self-propelled particles. We show that, as the hierarchy becomes important, the swarming transition changes from the weak first-order transition observed for egalitarian populations, to a stronger first-order transition for intermediately strong hierarchies, and finally the discontinuity reduces until vanish, where the order-disorde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Alongside the previous concerns, here we aim to clarify the nature of all PTs in the Vicsek model. By adopting the structural order parameter [18] and the technique of PDF segmentation [16], we confirm that all PTs between the two neighboring phase are first-order given the system is large enough. The existing problem is that the structural order parameter is still insensitive to the parameter change in some regions that makes the PDF segmentation bad and thus less precise in characterizing the PTs.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Alongside the previous concerns, here we aim to clarify the nature of all PTs in the Vicsek model. By adopting the structural order parameter [18] and the technique of PDF segmentation [16], we confirm that all PTs between the two neighboring phase are first-order given the system is large enough. The existing problem is that the structural order parameter is still insensitive to the parameter change in some regions that makes the PDF segmentation bad and thus less precise in characterizing the PTs.…”
Section: Discussionmentioning
confidence: 67%
“…In fact, there are three rather than simply two phases (ordered and disordered), i.e. the disordered gas-like state, the ordered liquid-like state, and the coexistence of ordered bands and disordered gas due to the density-velocity feedback [15,16]. More recently, with Eigen microstates approach, reference [17] revealed that the PT in the Vicsek model is essentially a hybrid of continuous and discontinuous PTs, but the discontinuous component dominates as the system size goes infinity.…”
Section: Introductionmentioning
confidence: 99%
“…This function enables us to distinguish first and second order phase transitions, such that it is continuous in second order transitions, while it shows a very sharp discontinuity for first order phase transitions, see for example [26]. We see this function for two β values in Fig.…”
mentioning
confidence: 85%
“…This reveals that the system exhibits a discontinuity at the point where the second peak is born (λ [13,14,22]. As a standard approach for bimodal PDFs [26], we divide the data at the valley point between s * 1 and s * 2 (with PDFs represented by P 1 (s * ) and P 2 (s * ) respectively), and average to find two s * i , i = 1, 2 for two branches (this enables us find the structure of the transition, otherwise a structure like β = 0 case is obtained, see Fig. 3 in the SM).…”
mentioning
confidence: 99%
“…However, a consensus is that our society is more often composed by heterogeneous individuals where they differ in many aspects such as their occupations, social statuses, cultural backgrounds etc [24] that potentially affect their decision-makings. The statement is also true in nature, like the reported examples homing pigeons [25] and white storks [26], where a small fraction of the group take the lead of decision-making regarding their movement direction and the soical hierachy potentially affects their swarming transitions [27]. Recently, researchers start to consider the impact of non-identical individuality and find that the population heterogeneity generally leads to better cooperation outcomes [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%